Evaluacion de arreglos agrosilvopastoriles en explotaciones ganaderas de la microrregion Bajo Magdalena - Roncallo Fandiño, B.=700 1 Barros Henriquez, J.; Bonilla B, R.; Murillo, J.; Del Toro, R.
(Es, En)
Ilus., 20 ref.
Keywords: SISTEMAS SILVOPASCICOLAS; EXPLOTACION AGRARIA; PRODUCCION ANIMAL; LEGUMINOSAS; GRAMINEAS; FAUNA DEL SUELO; CONTENIDO DE MATERIA SECA; CALIDAD; LECHE; COLOMBIA; REVISTA CORPOICA